Finance Sustainability of Entities of Small and Medium Business Working in Trade - N. V. Sedova (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The current situation in Russian economy advances serious demands to small and medium enterprises. The author of the article suggests plotting a finance plan at enterprises in accordance with the set goals and requirements of today’s economy in order to minimize uncertainty of the market environment and its adverse affects. The finance plan can help them balance their expenses and attain profit growth, which can contribute to winning new positions on market. Small and medium enterprises are characterized by good flexibility, which gives them an opportunity to adapt to the changing situation on market and stay competitive in any conditions. Small and medium entrepreneurship fosters a drop in unemployment by increasing the number of jobs, raising the volume of goods and services on market, which can have a positive impact on the social sphere. Enterprises of small and medium business are an integral part of healthy competition on market and it means an opposition to monopolies, free development and diversity in property forms. Small and medium business support investment activity at the expense of re-distribution of resources into the sphere of small and medium enterprises.